2014
DOI: 10.5301/ijao.5000266
|View full text |Cite
|
Sign up to set email alerts
|

Serum Tumor Markers in Hemodialysis Patients

Abstract: Aims The main objective of this work was to evaluate the influence of end-stage renal disease (ESRD) on concentrations of five tumor markers (TMs): carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9 (CA19-9), CA15-3, CA125, and prostate specific antigen (PSA) in a group of chronic hemodialysis patients (CHPs); and to study the influence of hemodialysis (HD) sessions on concentrations of the same TMs. Methods We compared TMs levels in CHP before HD sessions to a control group of 50 healthy volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…On the other hand our results are similar from the authors with Maoujoud et al [18] evaluated the influence of ESRD on concentrations of five tumor markers, including PSA, in 76 patients maintained on low-flow HD. They found that PSA levels were higher in the HD group (n = 76), compared with the control group of healthy volunteers (n = 50); no statistically significant difference was observed between the groups (p = 0.271).…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand our results are similar from the authors with Maoujoud et al [18] evaluated the influence of ESRD on concentrations of five tumor markers, including PSA, in 76 patients maintained on low-flow HD. They found that PSA levels were higher in the HD group (n = 76), compared with the control group of healthy volunteers (n = 50); no statistically significant difference was observed between the groups (p = 0.271).…”
Section: Discussionsupporting
confidence: 81%
“…modifying the material of membrane or changing in pore diameter; cancer markers with a small molecular weight overpass filter, resulting in reduction of their serum concentrations. Some studies demonstrated that PSA level is not alternated in hemodialysis patients, [48][49][50] although other authors observed an increase in total PSA and in PSA index in this population. 51 Perhaps, the different results seen in the studies mentioned above are due to the different ages of the patients enrolled.…”
Section: Acute Tumor Lysis Syndromementioning
confidence: 83%
“…[46][47][48][49][50][51][52] As regards CA125, some authors observed that the increase concentration of this tumor marker after HD treatment might be gender specific (in male patients), 44 others hypothesized a relationship between elevated CA125 levels and HCV infection. 52 Further studies are needed to evaluate the diagnostic and prognostic value of tumor markers in order to avoid misdiagnosis and unnecessary diagnostic investigations in the presence of renal impairment.…”
Section: Acute Tumor Lysis Syndromementioning
confidence: 99%
“…However, it has been reported that diagnosis and treatment should be considered according to the patient's clinic after the PSA test was measured high (3). Majoud et al reported that post-dialysis PSA levels were higher than pre-dialysis significantly (12). There are also studies reporting that there is no significant difference in serum PSA levels analysed before and after hemodialysis (13,14).…”
Section: Discussionmentioning
confidence: 99%